Delayed acute onset post traumatic sigmoid sinus/cerebral venous thrombosis - K. S., Bopaiah; Shah, Shreykumar P. (International Surgery Journal, 2017)
Post traumatic Sinus/cerebral venous thrombosis is a rare entity. A high index of suspicion is required as the prognosis is poor in this clinical setting, in view of the effects of the head injury. We report 2 cases of the patient worsening acutely after initial recovery from trauma. The etiology and pathogenesis in such cases are varied and hypothetical with no definite underlying cause identified. Cerebral venous thrombosis (CVT) as an etiology of headache is not always easy to diagnose unless suspected, and in any patient with head injury and delayed deterioration after initial recovery, post traumatic Cerebral venous thrombosis should be kept as a differential diagnosis.